Reconfiguring human resource development in the Caribbean : beyond the global marketplace - Greene, Edward (2007)
Suggests a framework that could inform the reconfiguration of human resources in the region. Opines that in planning for HRD development in the core inter-related elements of health, education and labour, provision ought to be made for outcomes that pay attention to gender equity, culture and development. Indicates that efforts geared to HRD cannot ignore the world of culture because it is an essential ingredient of reconfiguration. Sees cultural policies as a key to the creative management of human resources.